West Nile virus emergence in humans in Extremadura, Spain 2020 - Macias, Alicia; Martín, Paloma; Pérez-Olmeda, Mayte; Fernández-Martínez, Beatriz; Gómez-Barroso, Diana; Fernández, Esperanza; Ramos, Julian Mauro; Herrero, Laura; Rodríguez, Saray; Delgado, Elena; Sánchez-Seco, Maria Paz; Galán, Miguel; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
In Spain, the largest human West Nile virus (WNV) outbreak among humans was reported in 2020, constituting the second most important outbreak in Europe that season. Extremadura (southwestern Spain) was one of the affected areas, reporting six human cases. The first autochthonous human case in Spain was reported in Extremadura in 2004, and no other human cases were reported until 2020. In this work, we describe the first WNV human outbreak registered in Extremadura, focusing on the most important clinical aspects, diagnostic results, and control actions which followed. In 2020, from September to October, human WNV infections were diagnosed using a combination of molecular and serological methods (an in-house specific qRT-PCR and a commercial ELISA for anti-WNV IgM and IgG antibodies) and by analysing serum, urine, and/or cerebrospinal fluid samples. Serological positive serum samples were further tested using commercial kits against related flaviviruses Usutu and Tick-borne encephalitis in order to analyse serological reactivity and to confirm the results by neutralisation assays. In total, six cases of WNV infection (five with neuroinvasive disease and one with fever) were identified. Clinical presentation and laboratory findings are described. No viral RNA was detected in any of the analysed samples, but serological cross-reactivity was detected against the other tested flaviviruses. Molecular and serological methods for WNV detection in various samples as well as differential diagnosis are recommended. The largest number of human cases of WNV infection ever registered in Extremadura, Spain, occurred in 2020 in areas where circulation of WNV and other flaviviruses has been previously reported in humans and animals. Therefore, it is necessary to enhance surveillance not only for the early detection and implementation of response measures for WNV but also for other emerging flaviviruses that could be endemic in this area.